Salinity Inhibits Rice Seed Germination by Reducing α-Amylase Activity via Decreased Bioactive Gibberellin Content - Liu, Li; Xia, Weili; Li, Haixia; Zeng, Hanlai; Wei, Benhui; Han, Suoyi; Yin, Changxi (Frontiers in Plant Science, 2018)
Seed germination plays important roles in the establishment of seedlings and their subsequent growth; however, seed germination is inhibited by salinity, and the inhibitory mechanism remains elusive. Our results indicate that NaCl treatment inhibits rice seed germination by decreasing the contents of bioactive gibberellins (GAs), such as GA1 and GA4, and that this inhibition can be rescued by exogenous bioactive GA application. To explore the mechanism of bioactive GA deficiency, the effect of NaCl on GA metabolic gene expression was investigated, revealing that expression of both GA biosynthetic genes and GA-inactivated genes was up-regulated by NaCl treatment. These results suggest that NaCl-induced bioactive GA deficiency is caused by up-regulated expression of GA-inactivated genes, and the up-regulated expression of GA biosynthetic genes might be a consequence of negative feedback regulation of the bioactive GA deficiency. Moreover, we provide evidence that NaCl-induced bioactive GA deficiency inhibits rice seed germination by decreasing α-amylase activity via down-regulation of α-amylase gene expression. Additionally, exogenous bioactive GA rescues NaCl-inhibited seed germination by enhancing α-amylase activity. Thus, NaCl treatment reduces bioactive GA content through promotion of bioactive GA inactivation, which in turn inhibits rice seed germination by decreasing α-amylase activity via down-regulation of α-amylase gene expression.